Використання різних методичних підходів до оцінювання ризику неплатоспроможності транспортного підприємства в АР Крим - Зубкова, В.І; Миронович, М.С. (Культура народов Причерноморья, 2013)
В статті розглядається проблема ризику втрати платоспроможності підприємств, джерела та причини його виникнення, методи ухилення від ризику неплатоспроможності. Основна частина статті присвячена вивченню методів оцінок ризику неплатоспроможності підприємства, а саме аналіз платоспроможності на підставі розрахунку коефіцієнтів ліквідності й розподілення підприємств за зонами платоспроможності, які були вибрані як найбільш підходящі для транспортного підприємства АР Крим. Ключові слова: ризик неплатоспроможності, коефіцієнти ліквідності, зони платоспроможності, дебіторська заборгованість. В статье рассматривается проблема риска потери платежеспособности предприятий, источники и причины его возникновения, методы уклонения от риска неплатежеспособности. Основная часть статьи посвящена изучению методов оценок риска неплатежеспособности предприятия, а именно анализ платежеспособности на основании расчета коэффициентов ликвидности и распределение предприятий по зонам платежеспособности, которые были выбраны как наиболее подходящие для транспортного предприятия АР Крым. Ключевые слова: риск неплатежеспособности, коэффициенты ликвидности, зоны платежеспособности, дебиторская задолженность. The article is devoted to the insolvency risk, its reasons and influence on the company’s counterparties. Much attention is given to estimation of insolvency risk. As basic methods of the estimation were chosen: analysis of solvency based on liquidity(calculation of absolute, rapid and current liquidity ratios) ratios, analysis of solvency based on the coefficients of financial stability(calculation of coefficients of financial autonomy, financing, maneuverability of property asset, to material well-being by the personal funds). Such estimation of solvency is most widespread. Further the author analyzes an alternative method developed by Russian scientists. This method consists in distribution of enterprises into four zones, depending on the level of their solvency. The zones are: absolute, current, critical solvency and insolvency. The author estimates solvency of a transporting enterprise using analyses of its accounts receivable. All coefficients were practically calculated from data of activity of the enterprise. This method was chosen because it is considered to be the most adopted to insolvency risk estimation of a transporting company in the Crimea. In conclusion the author offers the ways of avoiding insolvency risk. Keywords: risk of insolvency, liquidity ratios, zone solvency, receivables.